Trends in Sentencing of Federal Drug Offenders: Findings From U.S. District Courts 2002–2017 - Testa, Alexander (Journal of drug issues, 2021)
This study uses 16 years (2002–2017) of federal criminal drug sentences from the U.S. Sentencing Commission (USSC) to examine trends in two criminal sentencing outcomes: whether a defendant received a prison sentence and the length of a prison sentence. Logistic and ordinary least squares regression analyses were used to assess criminal sentencing outcomes. Moderation analyses are conducted to assess variation in sentencing for specific drug offenses over time. Results demonstrate that sentencing for federal drug crimes has become less severe over time. However, there is substantial heterogeneity in sentencing across different drug types, with pharmaceutical opioid cases receiving the least leniency over time regarding the incarceration decision and methamphetamine cases experiencing the lowest reduction in the length of prison sentences from 2002 to 2017. Finally, our analysis stratified by race/ethnicity suggested that there is heterogeneity in sentencing outcomes for federal drug offenders, conditional on racial and ethnic background.